PENGARUH MEDIA POWERPOINT DAN PENGETAHUAN AWAL TERHADAP HASIL BELAJAR PELAKSANAAN PEKERJAAN PEMBESIAN PADA SISWA KELAS XI TEKNIK KONSTRUKSI BANGUNAN SMK NEGERI 2 PEKANBARU. - Sukianto, Sukianto (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2011)
This research started from the low level of students’ outcome on the implementation of Iron Work at SMK Negeri 2 Pekanbaru.  It can be seen through the low level of studens’ score last three years that have an average score under Minimum Standard Score (KKM) it means that learning outcomes is not achieved as expected.  It was caused by learning outcomes is not appropriate.  Therefore, it done an effort to increase students’ learning outcome by using Powerpoint media.  This research has purpose to know whether Powerpoint media is higher than using wallchart media, result of early students’ knowledge is higher by using Powerpoint media than wallchart media and to see the interaction between early students' knowledge and Powerpoint media.    The population of this research is all of the students of XI grade that learn the Implementation of Iron Work.  Which consist of five classes.  The researcher took two classes as sample, they are XI grade of Building Construction Engineer 1 (TKB1) as experimental class and XI grade of Building Construction Engineer 2 (TKB2) as control class.  This research is queasy experiment.  The data collection technique uses multiple-choice test.  It tested with t-test as data analysis and Analysis of Variance (ANAVA).The results of this research shows: (1) students’ learning outcome by using Powerpoint media is higher than students’ learning outcome by using  wallchart media, (2) students' learning outcome early knowledge by using Powerpoint media is higher than using media wallchart media, (3) the students who has low early knowledge would get higher learning outcome by using Powerpoint media than using wallchart media, and (4) there is no interaction that is taught with Powerpoint media to early knowledge on students’ learning outcome.  The conclusion in this research is the effect of Powerpoint media and early knowledge can increase students’ learning outcome.